Pharmacological Aspects of Natural Quercetin in Rheumatoid Arthritis - Tang M; Zeng Y; Peng W; Xie X; Yang Y; Ji B; Li F (Dove Medical Press, 2022)
Mengshi Tang,1,* Yan Zeng,2,* Weijun Peng,3 Xi Xie,1 Yongyu Yang,4 Biting Ji,5 Fen Li1 1Department of Rheumatology and Immunology, the Second Xiangya Hospital, Central South University, Changsha, 410011, People's Republic of China; 2Department of Rheumatology, Yueyang Central Hospital, Yueyang, 414000, People's Republic of China; 3Department of Integrated Traditional Chinese & Western Medicine, The Second Xiangya Hospital, Central South University, Changsha, 410011, People's Republic of China; 4Department of Pharmacy, The Second Xiangya Hospital, Central South University, Changsha, 410011, People's Republic of China; 5Shanghai Jing'an District Dental Disease Prevention and Control Institute, Shanghai, 200040, People's Republic of China*These authors contributed equally to this workCorrespondence: Fen Li, Department of Rheumatology and Immunology, the Second Xiangya Hospital, Central South University, No. 139, Renmin Middle Road, Changsha, 410011, People's Republic of China, Email lifen0731@csu.edu.cnAbstract: Rheumatoid arthritis (RA) is a chronic autoimmune disease that can lead to severe joint damage, disability and mortality. Quercetin (QUE) is a natural flavonoid that is ubiquitous in fruits and vegetables. This article reviews the effect of QUE on articular and extra-articular manifestations of RA in vitro and in vivo. In general, for articular manifestations, QUE inhibited synovial membrane inflammation by reducing inflammatory cytokines and mediators, decreasing oxidative stress, inhibiting proliferation, migration and invasion, and promoting apoptosis of fibroblast-like synoviocytes (FLS), regulated autoimmune response through modulating Th17/Treg imbalance and Th17 cells differentiation, reducing autoantibodies levels and regulating ectonucleoside triphosphate diphosphohydrolase (E-NTPDase)/ectoadenosine deaminase (E-ADA) activities, reduced bony damage via lowering matrix metalloproteinase (MMP)-1, MMP-3, receptor activator of nuclear factor kappa B ligand (RANKL) expression and osteoclasts formation. For extra-articular manifestations, QUE could reverse the neurodegenerative processes of the enteric nervous system (ENS) and exhibited cytoprotective, genoprotective and hepatoprotective effects. In addition, we also summarize some contradictory experimental results and explore the possibility for these differences to form a sound basis for the clinical application of QUE for RA.Keywords: rheumatoid arthritis, quercetin, pharmacological